SIMULASI ALAT ELEKTROSTIMULATOR AKUPUNTUR BERBASIS MIKROKONTROLER ATMega16 - Evrita Lusiana Utari; Irawadi Buyung; I Made Gde Gosali Putra (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Elektrostimulator combined in acupunture therapy to provide the stimulation of electric energy at the point of the meridians of the body. Granting the power to create a balance of energy (chi) in the body. In administering the energy must pay attention to the voltage waveform, intensity, frequency and timing of stimuli. The purpose of this research is to change the system tools from analog into digital by changing the settings of the timer and frequency using the keypad that is controlled using the Microcontroller ATMega16. Specifications of the simulation tool elektrostimulator acupunture designed include the frequency setting of 5-100Hz, setting the intensity of a voltage 0 timer setting until 25Vac 60 minutes and has a spike waveform mode continou and electrodes used floating types. The test result show that simulated acupunture elektrostimulator tool result obtained in accordance with the compliance with the specifications but there is little the percentage error of frequency deviation i.e. 0.47% deviation of the timer of 0.29%, intensity of the voltage deviation of 0.073 % and waveform was nearing the same against his theory.